Direct oral anticoagulant plasma level measurement in clinical practice: A French single-institution retrospective study. Issue 200 (April 2021) - Caré, Weniko; Foissaud, Vincent; Lefeuvre, Leslie; Daban, Jean-Louis; Vodovar, Dominique; Aletti, Marc; Doutrelon, Caroline
Abstract: Introduction: To describe patient characteristics and clinical situations where DOAC assays were ordered and determine whether the assays indications and subsequent patient management were consistent with current guidelines. Methods: Retrospective study of data from patients with prescriptions for three DOACs: dabigatran, rivaroxaban and apixaban treated at Percy Military Hospital (France) between 2016 and 2019. Results: During the study period, 196 DOAC measurements were performed on 148 patients (median age: 82.5 years). The most frequently prescribed DOAC was rivaroxaban (57.5%) and the commonest indication was nonvalvular atrial fibrillation (77%). Measurements were performed on 3.5% of patients with an active prescription for DOAC, and DOAC prescriptions complied with the product's characteristic summary in 62.8% of cases. The number of assays performed increased 2.5-fold between 2017 and 2019. Most DOAC assays were ordered due to emergency surgery or procedures (46.9%), bleeding (19.9%) or a risk of drug accumulation (13.8%). Time from the last DOAC dose to sample collection was specified in the medical file in only 25.5% of cases. Reasons for ordering DOAC measurements were consistent with the guidelines in 87.2% of cases. Subsequent clinical decisions were consistent with the guidelines in 86.2% of cases. Conclusions: DOAC assays ordering frequency was rare but increased during study. Acute clinical situations were the most common source of test orders. A correct interpretation of the results and subsequent management occurred in most but not all cases, indicating the need for additional education for physicians to raise awareness about tests indications and results interpretation. Highlights: Information DOAC measurements in clinical practice is scarce. We reviewed all DOAC measurements performed at our institution. Acute clinical conditions were the most frequent reasons to order DOAC assays. Context-dependent interpretation of the results was a source of errors.